Macroeconomics Post-GFC - Iwan Jaya Azis (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2019)
The core model of macroeconomics we teach in colleges and universities uses incredible assumptions to reach absurd conclusions. Among those assumptions are, no financial frictions such as credit rationing, individuals had rational expectations or acted as if they did, and representative agent to represent an aggregation of firm or household sector whose optimizing behaviors are micro-founded. With no financial frictions, the model fails to explain a major event such as the 2008 GFC. Why small shocks can have very large effects (amplification) that last so long (persistence), and why deep downturns can occur repeatedly with powerful spillovers and contagion effects? Constructed for analyzing only small fluctuations, the current core model is likely to provide little guidance as to what should be done in response. In this paper, I argue that the key problem with the current macroeconomics is the superficiality of its treatment towards financial sector. It is shown that financial frictions played a significant role in capital flows fluctuations, external shocks created channels of spillover and contagion across countries and across asset classes, capital flows with the presence of financial frictions made monetary policy more challenging, and they could be detrimental to financial stability and the distribution of income. Corrections and adjustments to existing core macroeconomic model should be based on empirical evidence and how the economy works, not on the esthetic riddles of established paradigm.